Through the eyes of a man: The analysis of female roles in Photocopier’s movie (2021) - Admiral Indra Supardan; Mochamad Edwin Iskandar (Priviet Social Sciences Journal, 2026)
This study examines the representation of Laura Mulvey’s male gaze in the Indonesian film Photocopier (2021), directed by Wregas Bhanuteja, through the framework of visual pleasure and narrative cinema. Other studies on Photocopier have explored semiotic representation, technology-enabled objectification, multimodal communication, critical discourse analysis, and cinematic techniques. However, none of them have systematically disclosed the psychoanalytic mechanisms of scopophilic pleasure and narcissistic identification occurring in the film’s narrative structure. This study employs a qualitative approach that combines Mulvey’s male gaze theory, Bordwell and Thompson’s film analysis method, Fairclough’s critical discourse analysis, and Rose’s visual methodology. This study scrutinizes selected scenes involving sexual harassment, objectification, and male-female interactions. The findings reveal that male characters systematically perform scopophilic violence through digital technology while continuously constructing narcissistic self-images disguised as artistry, paternalism, or economic survival. Notably, the film refuses to reproduce scopophilic pleasure for its audience through its cinematography. The film positions viewers as empathetic witnesses rather than voyeurs. The study further highlights how the copier machine functions as a central metaphor in this narrative, transforming from an instrument of violation into a tool of feminist resistance, as shown in the final scenes. These findings offer a meaningful contribution to the growing psychoanalytic film discourse within Indonesian cinema scholarship. Furthermore, this study proves that Mulvey’s concept is not a finished framework but rather a generative one. It requires cultural and technological adaptation when applied beyond its original Western context.